Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2515-7639/ab6c34
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between mobility and magnetoresistance in Weyl and Dirac semimetals

Abstract: The discovery of Weyl and Dirac fermions in solid systems is a recent major breakthrough in the field of condensed matter physics. These materials exhibit extraordinary properties in terms of carrier mobility and magnetoresistance (MR). These two quantities are highly dependent in the Weyl semimetal transition monopnictide family, i.e. NbP, TaP, NbAs, and TaAs. Furthermore, the gathered mobility and MR (or slope of MR) at 2 K in 9 T of other well-known Weyl and Dirac semimetals follow a relation similar to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…After that, we find that the m of the sample in the I 0 state has a relatively high value, in good agreement with other reported Weyl semimetals. 42,45 The pressure range of high carriers is roughly consistent with the reported pressure range where Weyl semimetals appear from theoretical calculations. 26 Owing to the Weyl semimetallic character of the materials, the conduction and valence bands generally cross each other near the Fermi energy, and there is a unique degeneracy.…”
Section: Resultssupporting
confidence: 83%
“…After that, we find that the m of the sample in the I 0 state has a relatively high value, in good agreement with other reported Weyl semimetals. 42,45 The pressure range of high carriers is roughly consistent with the reported pressure range where Weyl semimetals appear from theoretical calculations. 26 Owing to the Weyl semimetallic character of the materials, the conduction and valence bands generally cross each other near the Fermi energy, and there is a unique degeneracy.…”
Section: Resultssupporting
confidence: 83%
“…Various studies in NbP, TaP, NbAs, and TaAs have reported prominent properties of MR in the range of 10 4 %–10 6 % [ 9,16,18,19,37 ] as well as Nernst thermopower ( S xy ) of ≈1 × 10 3 μV K –1 , [ 16,21,23 ] which represent remarkable progresses among different types of topological semimetals. [ 35,38–53 ] Taking NbP as the example, the MR of single‐crystal NbP reaches an extremely large value of 8.5 × 10 5 % at 1.85 K in a magnetic field of 9 T, [ 9,37 ] which is ascribed to the interplay of overlapped conduction and valence bands, linear band dispersion and ultra‐high carrier mobility (μ) of 5 × 10 6 cm 2 V –1 s –1 .…”
Section: Introductionmentioning
confidence: 99%
“…First, the most significant driver of large LMR is high mobility. A correlation between mobility and MR% was previously observed across a range of TSM materials [3]. In this paper we control mobility within a single system.…”
Section: Discussionmentioning
confidence: 64%
“…Three dimensional topological semimetals (TSMs) exhibit linear and gapless bulk band dispersions along with topologically protected surface states arising from the band inversion [1]. In particular, topological protection against carrier backscattering is thought to help support high electron mobilities that have been measured up to 10 7 cm 2 /Vs in the Dirac semimetal Cd 3 As 2 and 10 5 -10 6 cm 2 /Vs in the Weyl semimetal family of (Ta,Nb)(As,P) [2,3]. These materials also typically feature Fermi levels near the band touching nodes (∼100 meV) coupled with large Fermi velocities, which can only occur in systems with nonparabolic bands.…”
Section: Introductionmentioning
confidence: 99%